Extreme Hydrological Events: New Concepts for Security - Vasiliev, O.F.; van Gelder, P.H.A.J.M.; Plate, E.J.; Bolgov, M.V.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2007)
This proceedings contains the papers which were presented at the NATO Advanced Research Workshop (ARW) on Extreme Hydrological Events: New Concepts for Security, which was held in Novosibirsk, Russia, from July 11-15, 2005. The workshop fell within the NATO priority research topic on Environmental Security, Disaster Forecast and Prevention. At the present time, the necessity of considerable deepening of our understanding about the nature of extreme and catastrophic natural and man-induced events, in particular hydrologic ones, becomes very topical, as well as the development of advanced methods for their prediction, including estimating probability of their occurrence and a risk related to them. Another aspect of this hydrological problem is reducing of vulnerability of social, economic, and engineering systems to the extreme hydrologic events (EHE) and decreasing of a degree of their effect on such systems. Dealing with these problems needs further refining existing tools for prediction and forecasting of EHE. It can be done essentially through revealing mechanisms of their generation and with use of new approaches and methodologies in related branches of hydrology. This ARW is targeted to contribute to the critical analysis and assessment of current knowledge on a number of the key issues of hydrology, such as: extreme hydrological phenomena, problems of floods, low flows and droughts. In view of significant economic losses and actually wide geographical occurrence, investigation of these hydrological phenomena is of great scientific and practical importance.
THOUGHTS ON THE ECONOMICS OF FLOODPLAIN DEVELOPMENT IN THE U.S. -- FLOOD RISK MANAGEMENT FOR SETTING PRIORITIES IN DECISION MAKING -- Basin case studies on extreme hydrological events -- RHINE FLOODS AND LOW FLOWS -- AUGUST 2002 CATASTROPHIC FLOOD IN THE CZECH REPUBLIC -- LESSONS LEARNED FROM THE ELBE RIVER FLOODS IN AUGUST 2002 - WITH A SPECIAL FOCUS ON FLOOD WARNING -- FLOODS IN AUSTRIA -- THE CONDITIONS OF THE FORMATION AND DEVELOPMENT OF EXTREME FLOODS IN ZAKARPATYE (THE BASIN OF THE TISA RIVER) -- SUMMER 1997 FLOOD IN POLAND IN PERSPECTIVE -- FLOODS IN SIBERIAN RIVER BASINS -- RAIN FLOODS OF THE FAR EAST AND EAST SIBERIA -- Probabilistic estimation in flood studies -- THEORY OF EXTREME EVENTS AND PROBABILITY DISTRIBUTIONS OF FLOODING CHARACTERISTICS -- REGIONAL FLOOD FREQUENCY ANALYSIS -- PROBABILISTIC FORECASTS USING BAYESIAN NETWORKS CALIBRATED WITH DETERMINISTIC RAINFALL-RUNOFF MODELS -- PREDETERMINATION OF FLOODS -- STATISTICAL ESTIMATION METHODS FOR EXTREME HYDROLOGICAL EVENTS -- Ice-induced floods -- STUDIES OF ICE JAM FLOODING IN THE UNITED STATES -- LABORATORY MODELLING OF ICE JAM FLOODS ON THE LENA RIVER -- HYDROLOGICAL CONDITIONS FOR ACTIONS ON PREVENTION OF ICE FLOODING ON THE LENA RIVER -- INFORMATION NEEDS WHEN ESTIMATING ICE JAM FLOODS AND ICE RUNS -- River low flows and climatic conditions and environmental issues -- DROUGHT-INDUCED WATER SCARCITY IN WATER RESOURCES SYSTEMS -- RIVER LOW FLOWS IN AUSTRIA -- ASSESSMENT OF THE EFFECT OF AUTUMN-WINTER RIVER LOW FLOW ON THE OPERATION OF A RESERVOIR WITH SEASONAL REGULATION -- Risk assessment and management for floods, low water events, damages vulnerability issues -- THE DUTCH STRATEGY FOR SAFETY AND RIVER FLOOD PREVENTION -- FLOOD CONTROL SYSTEMS IN RUSSIA -- EVACUATION AND LIFE-LOSS ESTIMATION MODEL FOR NATURAL AND DAM BREAK FLOODS -- FLOOD PROTECTION AND MANAGEMENT IN THE NETHERLANDS -- HYDRAULIC BOUNDARY CONDITIONS IN THE NETHERLANDS, AT PRESENT AND IN FUTURE -- REVISED STRATEGIES FOR FLOOD RISK MANAGEMENT: LESSONS FROM THE 2002 FLOOD IN EUROPE -- THE NATO WORKSHOP (3z(BEXTREME HYDROLOGICAL EVENTS(3y(B, NOVOSIBIRSK, RUSSIA, 10-15 JULY 2005 -- Conclusions and recommendations -- WORKING GROUPS CONCLUSIONS AND RECOMMENDATIONS.s
Keywords: Engineering; Environmental management; Civil engineering; Water pollution; Engineering; Civil Engineering; Water Policy/Water Governance/Water Management; Waste Water Technology / Water Pollution Control / Water Management / Aquatic Pollution; Electronic books